The Comprehensive Checklist of the Earthworm Genus Metaphire (Oligochaeta: Megascolecidae) in Vietnam - Quoc T. Phan; Dang H. Lam; Anh D. Nguyen (Species Diversity)
The checklist comprises 66 species/subspecies of the earthworm genus Metaphire Sims and Easton, 1972 in Vietnam. Of 66 species, 47 were described by samples from Vietnam and considered to be endemic species to the Vietnam fauna. The genus Metaphire is more distributed in southern Vietnam in comparison to other parts of Vietnam (32 species in the southern part, 31 species in the central part, and only 19 species in the northern part).